Overexpression of Hippo pathway effector TAZ in tongue squamous cell carcinoma: correlation with clinicopathological features and patients' prognosis. (29th March 2013) - Wei, Zicheng; Wang, Yanling; Li, Zhongwu; Yuan, Chunping; Zhang, Wei; Wang, Dongmiao; Ye, Jinhai; Jiang, Hongbin; Wu, Yunong; Cheng, Jie
Abstract : Background: Transcriptional coactivator with PDZ‐binding motif (TAZ) is a key downstream effector of Hippo signaling pathway involved in stem cell differentiation and organ development. Recently, its deregulation has been linked to initiation and progression of various cancers. The purpose of this study was to investigate the expression of TAZ in tongue squamous cell carcinoma (TSCC) and its prognostic value in predicting patients' outcomes. Methods: TAZ expression and localization in a panel of TSCC cell lines and human immortalized oral epithelial cell (HIOEC) were determined by real‐time RT‐PCR, western blotting, and immunofluorescence. In 52 TSCC tumor specimens with detailed clinical and follow‐up data, TAZ abundance was examined by immunohistochemistry and its associations with clinicopathological parameters, Ki‐67 expression and patients' survival were further assessed. Results: TAZ mRNA and protein levels were significantly higher in TSCC cells and specimens than those in non‐cancerous cells and normal tongue mucosa. Overexpression of TAZ in TSCC was significantly associated with tumor size ( P  =   0.033), pathological grade ( P  =   0.026), clinical stage ( P  =   0.013), Ki‐67 expression ( P  =   0.0485), and reduced overall and disease‐free survival (Kaplan–Meier analysis, log‐rank test, P  =   0.020, 0.019, respectively). Multivariate Cox regression analysis identified TAZ as an important independent predictor for survival of patients with TSCC [HR (hazard ratio), 4.351; 95% CI (95% confidence interval), 1.477–12.819; P  =   0.008]. Conclusion: Our data indicate that aberrant TAZ overexpression is associated with key clinicopathological features and poor survival in TSCC. These results suggest that TAZ might play critical roles in tumorigenesis of TSCC and become a novel prognostic biomarker and potential therapeutic target for this malignancy.